System Continuance Success of the Local Electronic Government in Indonesia - Dody, Herdiana; A'ang, Subiyakto; Aedah, Abd Rahman (2022)
The adoption and use of electronic government (e-government) services are still limited in most countries as they are largely guided by supply-side factors. However, one of the technology-enabled modernization issues is that decision-makers do not take user expectations and preferences. Referring that the citizens’ needs have become the focus of attention, it makes sense to investigate the sustainability factors of the system from the perspectives of the users. This study aimed to determine the factors that influence the system continuance success of local e-government in Indonesia. We adopted, combined, and adapted the information system (IS) success model, the unified theory of acceptance and use of technology (UTAUT) model, the expectancy confirmation model (ECM) to develop the research model. Around 390 valid survey data were analyzed using the partial least square structural equation modeling (PLS-SEM) method. The findings showed that the user satisfaction, effort expectations, performance expectations, and system use factors affect system continuance success of the local e-government in Indonesia.